Model Matematika Penyebaran Hoax COVID-19 - Wahyudin Nur; Darmawati Darmawati (Journal of Mathematics: Theory and Applications, 2020)
In this article, the problem of spreading hoaxes during the corona-19 outbreak is studied using a mathematical model. Currently, we often see a lot of hoaxes that are very unsettling, for example the news that eggs are a corona drug. In addition, there have been denials of funerals for Covid victims in various regions. In this article, the impact of government education and outreach, decisive action against hoax spreaders and ignorance of people who understand the problem of Covid-19 regarding the spread of hoaxes. The model built using 4 compartments, equilibrium point, free hoax spreader, basic reproduction number and sensitivity analysis are discussed in this article. Several numerical simulations are provided to test the theoretical study of the model